Secondary production of Chasmagnathus granulatus (Crustacea; Decapoda) in a Ramsar Site from Argentina - César, Inés Irma (2007)
Secondary production of Chasmagnathus granulatus was calculated at the Refugio de Vida Silvestre Bahía Samborombón, Argentina (36° 16′ S and 57° 06′ W). Sampling was conducted on nine occasions between March 2001 and February 2003, crabs were collected by hand, physico-chemical variables, granulometry and organic matter contents of the sediments were registered. Crabs were classified as male, female and undifferentiated, measured (total carapace width: CW) and weighed (wet and dry weight: DW at 60 °C, during 48 hours). A correlation analysis between CW and DW was made. Morphometric growth of C. granulatus was by the application of the power function (y = a x b), where the carapace width (CW) was used as an independent variable. Males, females and undifferentiated individuals were analysed separately as well as all together as a group. The data were fitted indicating a positive allometry (constant of allometry b > 3), the males showing the greatest allometric value. The individuals (n = 957 juveniles and adults) were separated in cohorts by the polymodal width-frequency distribution converted into normal curves. Three cohorts were found during the whole study period, and two cohorts coexisting in each sampling date. Ovigerous females were caught on December 2001, 2002 and February 2003. The size-frequency method was used to estimate the annual production. The major contribution to production was carried out by the mature individuals, in particular those with size between 25 and 30 mm, but on the other hand, only few individuals measuring from 10 to 20 mm were collected. The annual production of C. granulatus was estimated in 7.76 g.m-2. The biomass (expressed as total dry weight) varied between 0.55 and 1.85 g.m-2, with the greater values being registered during autumn and spring, and the lower values during summer.